Dose-response effects of omega-3 on platelet aggregation: an observational study - Thomas Kander; Erik Lindblom; Ulf Schött (Journal of International Medical Research, 2018)
Objective This study aimed to evaluate the dose-response effects of supplemental omega-3 fatty acids on platelet function in healthy volunteers. Methods Twelve healthy volunteers ingested a normal supplemental dose of 1260 mg omega-3 fatty acids daily for 5 days, followed by a high dose of 2520 mg daily for another 5 days. Multiple electrode aggregometry (MEA) with four different agonists was used to measure platelet aggregation before and after the normal- and high-dose regimes. In vitro spiking using physiological doses of omega-3 fatty acids was also performed to determine whether MEA is capable of detecting a platelet-inhibiting effect due to omega-3 fatty acids. Results There were no differences in platelet aggregation measured by the MEA assay in healthy volunteers after intake of either the normal or high dose of omega-3 fatty acids. In the in vitro experiment, a platelet-inhibiting effect of omega-3 fatty acids was shown by an arachidonic acid agonist in MEA . Conclusions Supplemental omega-3 fatty acids do not evoke their positive health effects through inhibition of platelet aggregation measurable with MEA.